Assessment of the Contribution of Flooded Rice Cultivation Systems to Methane Emissions in the Lower Ouémé Valley, in Benin Republic - ADOUNKPE, GNONLONFOUN JULIEN; Ahoudji, Othniel; SINSIN, AUGUSTIN BRICE (My University, 2021)
Flooded rice cultivation fields appear to be the major source of methane emission. In Benin Republic, flooded rice is cultivated in the Niger River and Ouémé River Basins. The present study aims to assess the contribution of flooded rice cultivation systems to methane emissions in the lower Ouémé Valley. Methane emission calculation was based on Activity Data which is the flooded rice harvested surface area from 2008 to 2017. The Tier 2 methodology of the IPCC 2006 Guidelines’ and the complements of the “Refinement 2019” have been used to elaborate the specific emission factors for the lower valley of Ouémé and to estimate the emission of methane in this zone. Semi- structured interviews were conducted with producers in order to elaborate on their perceptions of gas emissions in the flooded rice fields. The EX-ACT tool was used to estimate the carbon footprint of the intensive rice cultivation system “SRI” and the conventional rice cultivation system “SRC”. It is shown that producers have a strong perception of gas emissions in rice fields but are totally unaware of the nature of the gas. Methane emitted in the lower valley of the Ouémé is around 528 tons/year between 2008 and 2017 while the carbon footprint resulting from the results of EX-ACT for the adoption of the SRI rises to the level of sequestration of approximately 0.4 tCH4/ha/year. The intensive rice cultivation system has been identified as the production system that minimizes methane emissions and maximizes rice production.
Keywords: Flooded Rice Cultivation; Methane; Lower Valley of Ouémé; Greenhouse Gases; Climate Change